2013
DOI: 10.1105/tpc.113.113605
|View full text |Cite
|
Sign up to set email alerts
|

From Endoplasmic Reticulum to Mitochondria: Absence of the Arabidopsis ATP Antiporter Endoplasmic Reticulum Adenylate Transporter1 Perturbs Photorespiration

Abstract: The carrier Endoplasmic Reticulum Adenylate Transporter1 (ER-ANT1) resides in the endoplasmic reticulum (ER) membrane and acts as an ATP/ADP antiporter. Mutant plants lacking ER-ANT1 exhibit a dwarf phenotype and their seeds contain reduced protein and lipid contents. In this study, we describe a further surprising metabolic peculiarity of the er-ant1 mutants. Interestingly, Gly levels in leaves are immensely enhanced (263) when compared with that of wild-type plants. Gly accumulation is caused by significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 68 publications
2
23
0
Order By: Relevance
“…2A and 2 B , Supplementary Material online). Glutaredoxin genes are involved in antioxidant defense and stimulate photorespiratory glycine decarboxylase activity in plant mitochondria ( Hoffmann et al 2013 ). Thus given the expression of the duplicate genes in BS cells, it is possible that they function to protect the cell from oxidative damage as a result of activation of photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…2A and 2 B , Supplementary Material online). Glutaredoxin genes are involved in antioxidant defense and stimulate photorespiratory glycine decarboxylase activity in plant mitochondria ( Hoffmann et al 2013 ). Thus given the expression of the duplicate genes in BS cells, it is possible that they function to protect the cell from oxidative damage as a result of activation of photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a redox-regulation mechanism was proposed and experimentally verified only for the Synechocystis GDC P-protein (Hasse et al, 2013), the actual Gly decarboxylase. It has also been shown that the entire GDC activity became severely inhibited in a more oxidized and reactive oxygen speciesproducing mitochondrion due to a defect in the endoplasmic reticulum-localized adenylate transporter 1 (ER-ANT1) in Arabidopsis and rice (Oryza sativa;Hoffmann et al, 2013;Zhang et al, 2016), which was partly relieved upon DTT addition (Hoffman et al, 2013). These findings stimulated us to test GDC-L (mtLPD) for its potential to undergo redox-regulation, which could be based on disulfide bond formation that has been in silico predicted onto the LPD structure (Faure et al, 2000).…”
Section: Trxo1 Contributes To Redox-regulation Of Gdc Through Lpdmentioning
confidence: 99%
“…The reverse, i.e. H 2 O 2 produced by the ER to be sensed within the mitochondrial matrix inducing glutathionylation of a Gly decarboxylase subunit, has been proposed recently (Hoffmann et al, 2013). A recent study suggests that the twin-Cys proteins At12cys1/2 can relocate from the mitochondria to cytosol and chloroplast upon Complex I dysfunction, providing a potential mechanism to signal mitochondrial dysfunction to the rest of the cell in plants (Wang et al, 2016).…”
Section: Considerations For Transduction Of Mtros Signals Out To the mentioning
confidence: 99%